THE CONCEPT OF HYPERACTIVITY. THE IMPACT OF HYPERACTIVITY IN EARLY SCHOOL AGE - Umrzaqova Gulchexra Abdurasuljon qizi (European Science Publishing, 2025)
This article examines the symptoms of hyperactivity, its causes, and the positive and negative effects it has on children of primary school age. Recommendations are given on how to approach hyperactive children by teachers and parents. It is also emphasized that by using pedagogical strategies when working with hyperactive children, their energy can be directed in a positive direction.
Keywords: Children, emotional intelligence, hyperactivity, characteristics, education, behavior, methods, educator, cognitive development, emotional health, interpersonal conflicts, inner strength.